Os limites da razão na formação das decisões jurídicas: a relação entre Direito e Moral revisitada à luz das novas teorias cognitivas sobre a formação do julgamento moral - Thais de Bessa Gontijo de Oliveira (2018)
The dissertation revisits the relationship between Morality and Law, a recurrent study object in Legal Studies. Even though there are many theoretical efforts to emancipate Moral Law, the main hypothesis advanced here is that, in light of the contemporary theories on human cognition, Jurisprudence an Morality are inextricably intertwined. This conclusion put forth within the perspective of Consilience, a research program that proposes a synthesis among all branches of knowledge to understand human behavior. The effort aligns not only traditional legal research methods (that put Jurisprudence in contact with Philosophy, with Politics, sometimes with Economy, Psychology, or with Fine Letters, that is, Humanities and Social Sciences), but also with other fields of knowledge with which the dialogue is not so straightforward: the Neurosciences, Biology, Primatology, Medicine, Computational Sciences. We assumed that, to know human behavior, disciplinary boundaries are more an obstacle to be overcome and this was the task of the thesis. By doing this, there are many problems open to this kind of investigation; among them, we decided to explore the possibility of pure rational judgments, particularly when the issue at hand is moralized, given that rational decisions - Reason - became an ideal pursued by the Jurisprudence. To answer this, we present some state of the art psychological theories (developed within Cognitive Sciences framework), that this pure rational judgment is a gross simplification of the mental complexity necessary to arrive at a decision in a nutshell, a myth. In order to do so, we have recovered the theory that proposed human beings have basically two ways of thinking (perhaps the most ancient and resilient psychological model in the history of ideas). At its contemporary version, Cognitive Sciences operate within a paradigm in which there are two modes of thinking: one that is fast and automatic (guided by biases, heuristics, intuitions and first impressions), called System 1, and the second which is slow and deliberative (based on cold reflections), called System 2. Contemporary Cognitive Sciences are largely concerned with the relationship between these two forms of thinking, and the subject is still under debate. Although there is no consensus, in one respect, most researchers seem to agree: the normal human does not make pure rational judgments. The purpose of the thesis is then to explore the legal consequences of this new paradigm